More than a syllable in fib-ROS-is: The role of ROS on the fibrotic extracellular matrix and on cellular contacts. (October 2018) - Grosche, Julius; Meißner, Juliane; Eble, Johannes A.
Abstract: Fibrosis is characterized by excess deposition of extracellular matrix (ECM). However, the ECM changes during fibrosis not only quantitatively but also qualitatively. Thus, the composition is altered as the expression of various ECM proteins changes. Moreover, also posttranslational modifications, secretion, deposition and crosslinkage as well as the proteolytic degradation of ECM components run differently during fibrosis. As several of these processes involve redox reactions and some of them are even redox-regulated, reactive oxygen species (ROS) influence fibrotic diseases. Redox regulation of the ECM has not been studied intensively, although evidences exist that the alteration of the ECM, including the redox-relevant processes of its formation and degradation, may be of key importance not only as a cause but also as a consequence of fibrotic diseases. Myofibroblasts, which have differentiated from fibroblasts during fibrosis, produce most of the ECM components and in return obtain important environmental cues of the ECM, including their redox-dependent fibrotic alterations. Thus, myofibroblast differentiation and fibrotic changes of the ECM are interdependent processes and linked with each other via cell-matrix contacts, which are mediated by integrins and other cell adhesion molecules. These cell-matrix contacts are also regulated by redox processes and by ROS. However, most of the redox-catalyzing enzymes are localized within cells. Little is known about redox-regulating enzymes, especially the ones that control the formation and cleavage of redox-sensitive disulfide bridges within the extracellular space. They are also important players in the redox-regulative crosstalk between ECM and cells during fibrosis.